Răspuns:
Explicație pas cu pas:
a. 4(x+3)-7x=5(2-x)+18
4x + 12 - 7x = 10 - 5x + 18
-3x + 12 = 28 - 5x
5x - 3x = 28 - 12
2x = 16
x = 16 : 2 = 8
________________
b. 5x-7(7x+1)=3(3-2x)+8
5x - 49x - 7 = 9 - 6x + 8
5x - 49x + 6x = 7 + 9 + 8
-38x = 24
x = -24/38 = -12/19
___________________
c. 2(x+3)+5(1-2x)=2-x-3(x+1)
2x + 6 + 5 - 10x = 2 - x - 3x - 3
-8x + 11 = -4x - 1
8x - 4x = 11 + 1
4x = 12
x = 12 : 4 = 3
___________________
d. 3(x+4)-5(2x+1)=4(x+3)-6(2x+3)+5
3x + 12 - 10x - 5 = 4x + 12 - 12x - 18 + 5
-7x + 7 = -8x -1
8x - 7x = -7 - 1
x = -8